Fibra na alimentação do jundiá (Rhamdia quelen) - Pedron, Fabio de Araújo (2006)
Two experiments were accomplished to study the crude fiber effect on the growth, digestive parameters, and yield and carcass quality of jundiá (Rhamdia quelen) juveniles. Six treatments were evaluated (3 replications) in which 2 sources (soy hull and cotton hull) and three levels of crude fiber (4,7,10%) were tested. In the first trial (120 days), 450 fish (129,11±7,8 g) were randomly distributed in 18 net cages with 1m3 at densities of 25 fish/cage, in 0.1 ha earth fishpond to verify the growth performance: weight, total length, weight gain (g/day), biomass, survival, carcass and fillet yield, digestive and hepatic-somatic indexes, intestinal quotient, with the chemical composition values of fillet, protein and fat deposition on fillet were calculated. No difference was detected in the growth performance. Fish fed with soy hull diets presented more fat and mineral accumulation on fillets (P<0.05). Decreasing linear effect on deposition of protein in fillet was detected with soy hull crude fiber increasing (P<0.05). In the second trial (digestibility essay) 48 fish (165.45 ±30g) were maintained in a water reuse system with 6 conic tanks (200L each). Was added 0.5% of chromo oxide (Cr2O3) as an inert marker in the same diets. The feces were collected and dried, to estimate apparent digestibility of crude protein, ether extract, drying material and neutral detergent fiber (NDF), in two water temperatures (18° C and 28° C). The digestibility values of nutrients showed themselves lower when water temperature is 18° C, compared to water temperature in 28° C. Soy hull (10%FB) causes reduction in crude protein digestibility and ether extract digestibility with 18°C. NDF and dry matter digestibility have the same behavior for the tested fiber sources, excepted to cotton hull 10%. In conclusion, the sources and fiber levels did not affect the jundiá s performance. The nutrients digestibility is better with 28°C water temperature.